STUDI PERBANDINGAN KEANEKARAGAMAN SOIL SEED BANK PADA LAPISAN KEDALAMAN YANG BERBEDA DI DAERAH BUDIDAYA LAHAN KERING DAN SAWAH - Azzahra Gusviani, Nisa; Gian juliano; Dini Hervani; Puan Habibah; Enriski Efrata (Jurnal Pertanian Agros, 2026)
Soil seed bank refers to seeds that remain dormant and are stored in the soil. One group of plants that commonly stores its seeds in the soil is weeds, which do so as a form of survival and reproduction strategy. This study aimed to analyze the diversity and density of weed soil seed banks at different soil depths in upland and paddy cultivation areas. The research was conducted in the horticultural and paddy field areas of Andalas University, Padang, from May to July 2022. Soil samples were collected using a purposive sampling method at depths of 0–10 cm, 10–20 cm, and 20–30 cm, with three replications for each land type. The data were analyzed descriptively by calculating relative density (KR), relative frequency (FR), summed dominance ratio (SDR), and importance value index (INP). The results showed that both weed species diversity and abundance decreased with increasing soil depth. In upland areas, Euphorbia hirta (patikan kebo) exhibited the highest SDR and INP values at depths of 0–10 cm and 10–20 cm, whereas in paddy fields, this species remained dominant despite a reduction in its population. No viable seeds were found at a depth of 20–30 cm in paddy soils. These findings indicate that variations in soil depth and land conditions significantly influence the composition and dominance of weed species, and such information can serve as a basis for developing effective and site-specific weed management strategies.